Varicose Veins and Homeopathy: A Natural Path to Relief (Homoeopathy for All, 2026)
Varicose veins are a common vascular  disorder characterized by dilated,  elongated, and tortuous superficial  veins, predominantly affecting the  lower extremities. This condition  arises due to valvular incompetence  leading to venous hypertension. The  present thesis explores the etiology,  pathophysiology, clinical features,  diagnosis, complications, and  management of varicose veins, with  a special emphasis on homoeopathic  therapeutics. Homoeopathy, based  on the principle of individualization,  offers a holistic approach in managing  varicose veins, particularly in early  and moderate stages. This study  integrates classical homoeopathic  literature with modern medical  understanding to provide a  comprehensive overview.
Keywords: Varicose; veins; vascular; disorder; characterized